Far-field Lorenz–Mie scattering in an absorbing host medium: Theoretical formalism and FORTRAN program - Mishchenko, Michael I.; Yang, Ping (Journal of quantitative spectroscopy & radiative transfer, 2018)
•We study electromagnetic scattering by spherical particles immersed in an unbounded absorbing medium.•A first-principles approach allows for the calculation of relevant far-field optical observables.•This approach is implemented in the form of a public-domain FORTRAN program. In this paper we make practical use of the recently developed first-principles approach to electromagnetic scattering by particles immersed in an unbounded absorbing host medium. Specifically, we introduce an actual computational tool for the calculation of pertinent far-field optical observables in the context of the classical Lorenz–Mie theory. The paper summarizes the relevant theoretical formalism, explains various aspects of the corresponding numerical algorithm, specifies the input and output parameters of a FORTRAN program available at https://www.giss.nasa.gov/staff/mmishchenko/Lorenz-Mie.html, and tabulates benchmark results useful for testing purposes. This public-domain FORTRAN program enables one to solve the following two important problems: (i) simulate theoretically the reading of a remote well-collimated radiometer measuring electromagnetic scattering by an individual spherical particle or a small random group of spherical particles; and (ii) compute the single-scattering parameters that enter the vector radiative transfer equation derived directly from the Maxwell equations.